ORGANIZATIONAL CHANGE IN MENTAL HEALTH CENTERS IN KAZAKHSTAN: A COMPARATIVE CASE STUDY OF NORTH AND EAST KAZAKHSTAN OBLASTS - Tuleussarinova, Saule; Altybayeva, Zhazira (Nazarbayev University Graduate School of Public Policy, 2020)
Kazakhstan faces significant challenges in the field of mental health care and currently, there is an ongoing reform, which aims at improving the overall situation with the provision of quality care and transforming the Mental Health Centers throughout the country. This master’s project is a cross-sectional comparative case study of the organizational changes in two Mental Health Centers of North and East Kazakhstan Oblasts, which are taking place as part of the ongoing reform. The main goal of this study is to determine and analyze the key factors that have affected the organizational changes, as well as evaluate the differences in organizational changes between the two selected Mental Health Centers using such data collection methods as survey and in-depth interviews. The research findings of this study have demonstrated that the Mental Health Center in the East region experiences more challenges in organizational changes than the Mental Health Center in the North. Moreover, this research has shown the importance of such factors of organizational change as effective communication, commitment to changes, top management support, provision of resources and effectiveness of institutional changes. Keywords: Mental health care, Mental Health Center, North Kazakhstan Oblast, East Kazakhstan Oblast, organizational changes, primary care.
Keywords: Mental health care; Mental Health Center; North Kazakhstan Oblast; East Kazakhstan Oblast; organizational changes; primary care; Research Subject Categories::MEDICINE; Research Subject Categories::SOCIAL SCIENCES; Research Subject Categories::LAW/JURISPRUDENCE